2021
DOI: 10.4315/jfp-20-492
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Profile of Severe Acute Respiratory Syndrome Coronavirus 2 in Canadian Food Sources

Abstract: A new coronavirus strain known as SARS-CoV-2 has spread throughout the world. This virus is the causative agent for the Coronavirus Disease 2019 (COVID-19) and spreads primarily through human-to-human transmission via infected droplets and aerosols generated by infected persons. While COVID-19 is a respiratory virus, the potential for transmission of SARS-CoV-2 via food is considered theoretically possible and remains a concern for Canadian consumers. We have conducted an exposure assessment of the likelihood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…It is important to note that the mere presence of genetic material of the virus in shellfish does not mean that an infection could take place. To date, no evidences for transmission linked to the ingestion of food exist, and the recent cases associated with frozen food imports reported in China (Han et al, 2021;Liu et al, 2020) are related to the presence of SARS-CoV-2 in the outer food package's surface, which would act as any other fomite (Rose-Martel et al, 2021). The international consensus indicated that it is highly unlikely that the ingestion of SARS-CoV-2 will lead to the disease so shellfish should not be considered a risk or a vector of SARS-CoV-2.…”
Section: Datementioning
confidence: 99%
“…It is important to note that the mere presence of genetic material of the virus in shellfish does not mean that an infection could take place. To date, no evidences for transmission linked to the ingestion of food exist, and the recent cases associated with frozen food imports reported in China (Han et al, 2021;Liu et al, 2020) are related to the presence of SARS-CoV-2 in the outer food package's surface, which would act as any other fomite (Rose-Martel et al, 2021). The international consensus indicated that it is highly unlikely that the ingestion of SARS-CoV-2 will lead to the disease so shellfish should not be considered a risk or a vector of SARS-CoV-2.…”
Section: Datementioning
confidence: 99%
“…Consequently, there is a hypothetical route of transmission that the contaminated cold food or food packaging material can transmit the virus, and an infected worker will spread the virus through “person-to-thing-to-person” (Han & Liu, 2021 ). However, it should be noted that SARS-CoV-2 identification is often achieved by rapid and sensitive molecular methods to detect viral RNA, but does not necessarily give any information on its infectivity (Rose-Martel et al, 2021 ). Moreover, the infectivity potency on food and food packaging of CoVs declines as time goes by (Li et al, 2021 ) and the chance of transmission through inanimate surfaces are very small (Goldman, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…While foodborne transmission of SARS‐CoV‐2 has not been shown, and is not predicted to be a likely cause of transmission (Rose‐Martel, et al 2021), food surfaces and food packaging may be able to act as fomites (O'Brien, et al 2020). In high‐activity areas where food is present, such as in grocery stores and restaurants, there is a possibility that SARS‐CoV‐2 from an infected individual or a food handler could be deposited onto food surfaces.…”
Section: Introductionmentioning
confidence: 99%